Tunjangan Kinerja, Motivasi dan Disiplin terhadap Kinerja Pegawai - Andriani Gani Balanehu; Lalu Satria Utama; Obed Bida (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the effect of performance allowances, motivation, and discipline on improving employee performance at the West Papua Regional Office of the Ministry of Law and Human Rights. This research uses a quantitative approach because it tests hypotheses objectively. This research was conducted at the West Papua Ministry of Law and Human Rights Regional Office. Data collection techniques include observation, interviews, and questionnaires using descriptive statistical data analysis techniques. The results of the research, partially the performance allowance, motivation, and discipline variables have a significant effect on employee performance in a simple regression model, while the results of the multiple regression test when other variables are taken into account, the performance allowance and motivation variables are not significant on employee performance because they are dominated by the discipline variable. However, simultaneously, the three variables together have a significant effect on employee performance. In conclusion, performance allowances, motivation, and discipline influence improving employee performance at the West Papua Regional Office of the Ministry of Law and Human Rights. Keywords: Discipline, Employee Performance, Motivation, Performance Allowances.